Long-Term Biochemical Control of a Prospective Cohort of Prostate Cancer Patients Treated With Interstitial Brachytherapy Versus Radical Prostatectomy. Issue 4 (April 2023) - Sanmamed, N.; Locke, G.; Crook, J.; Liu, A.; Raman, S.; Glicksman, R.; Chung, P.; Berlin, A.; Fleshner, N.; Helou, J.
Abstract: Aims: To report long-term oncological outcomes of men treated prospectively as part of the American College of Surgeons Oncology Group phase III Surgical Prostatectomy Versus Interstitial Radiation Intervention Trial (SPIRIT) at our institution. Materials and methods: In 2003–2004, patients eligible for SPRIT attended a multidisciplinary educational session, following which they could choose radical prostatectomy, low dose rate brachytherapy (LDR-BT) or randomisation to SPIRIT. Biochemical failure was determined by the accepted definitions of a prostate-specific antigen (PSA) level ≥0.2 ng/ml after radical prostatectomy and the Phoenix definition of PSA ≥2 ng/ml above the nadir after LDR-BT. A sensitivity analysis, using a PSA >0.5 ng/ml to define biochemical failure after LDR-BT and a threshold PSA ≥0.2 ng/ml, was carried out to test the robustness of the results. To account for the competing risk of death, Gray's test was used to test the equality of the cumulative incidence function of biochemical failure between treatment groups. The Kaplan–Meier method was used to estimate overall survival and prostate cancer-specific survival. A P -value ≤0.05 was considered statistically significant. Results: Of 156 patients, 100 received LDR-BT (15 after randomisation) and 56 underwent radical prostatectomy (15 after randomisation). The median follow-up was 12.6 and 14.7 years for LDR-BT and radical prostatectomy, respectively. The median age was 60 years; the median pre-treatment PSA was 5.5 (interquartile range 4.3–7.1). No significant differences in patient characteristics were found between groups. Two patients received adjuvant radiotherapy after radical prostatectomy. The cumulative incidence function of biochemical failure was 0%, 1.1% and 2.4% at 5, 10 and 15 years, respectively, in the LDR-BT arm versus 8.5%, 15.8% and 15.8% in the radical prostatectomy arm ( P < 0.001). These results were consistent when varying the definition of biochemical failure defined as PSA ≥0.5 ng/ml ( P = 0.01). At 15 years, overall survival was higher in patients treated with radical prostatectomy compared with those treated with LDR-BT; however, no statistical difference was found in prostate cancer-specific survival. Conclusion: In low-risk prostate cancer patients, LDR-BT offers excellent long-term oncological outcomes comparable with radical prostatectomy, in addition to the previously reported advantage for LDR-BT in urinary and sexual quality of life domains and patient satisfaction. Highlights: LDR-BT offers comparable biochemical control compared with radical prostatectomy for low-risk PCa. Overall survival at 15 years was higher for radical prostatectomy compared with LDR-BT. Long-term PCSS is equivalent for patients treated with LDR-BT or radical prostatectomy.